A Critical Analysis of Auguste Comte's Positivism for Islamic Digital Research - Mahmud Yunus Mustofa; Nadhifah Nadhifah; Abdul Djamil; Muhammad Faqih Irsyad (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2023)
Auguste Comte's Positivism, a philosophical paradigm that originated in the early 19th century, has been widely discussed and debated among scholars in various fields. In recent years, this issue has gained increasing attention in the context of Islamic digital research. This paper aims to critically analyze Comte's Positivism and its impact on Islamic digital research. In Islamic digital research, Positivism has been criticized for its lack of cultural and historical context and its disregard for the role of ethics and values. This article illustrates how positivism's emphasis on empirical observation and data is compatible with the Islamic digital research paradigm. Given the vast data generated by digital technologies, the scientific method provides a convincing foundation for comprehending complicated phenomena in the digital world. Findings indicate that applying positivism as a research paradigm in digital research is beneficial. However, digital researchers are advised to be cautious of the weaknesses of the paradigm they would adopt for a study.